Systematic Planning for Business Functions How to Develop Strategic Business Plans. - Butuner, Hakan (Productivity Press, 2026)
The book presents a framework of six steps through which each business passes, a pattern of procedures for straightforward planning, and the three fundamentals -- marketing strategy, operations strategy, and sensitivity analysis -- involved in any business planning project.